Orchidectomy Upregulates While Testosterone Treatment Downregulates the Expression of Ornithine Aminotransferase Gene in the Mouse Kidney - Levillain, Olivier; Dégletagne, Cyril; Letexier, Dominique; Déchaud, Henri (IntechOpen, 2011)
None